What is inclusive development? Introducing the multidimensional inclusiveness index - Christoph Dörffel; Sebastian Schuhmann (Friedrich Schiller University Jena, 2020)
Despite successes in mitigating global poverty, there is a growing objection against addressing development policies in many countries fed by the feeling of growing inequalities. Thus, development should be more "inclusive". The purpose of this paper is to address two major shortcomings of previous literature: First, a lacking agreement about what constitutes inclusiveness. Although the concept overall is not unambiguous, we show it needs to be human-centered at its core. Second: A suitable measurement for development. Prominent previous approaches like the Human Development Index (HDI) and Inclusive Development Index (IDI) have major conceptual drawbacks and lacking data availability. We create the Multidimensional Inclusiveness Index (MDI) that we deem conceptually more appropriate and that is available for a 50% larger sample than the HDI. The MDI is calculated in three versions for up to 171 countries for the years 1960-2018. For the aggregation of the two subindices that constitute the MDI - one on development equity and one on absolute development achievements - we avoid value judgements by applying principal component analysis. Subsequently, we chose a geometric aggregation method to calculate the MDI. We show that the MDI captures regional development patterns and that major events such as regime changes or genocides are reflected in country trends. Despite correlations resulting from the similarities in the data included, the larger set of information included in the MDI provide new insight when compared to the HDI, GDP or IDI data; its data availability is much larger compared to the HDI and IDI. The distinction into achievements and equity subindices delivers important information to disentangle countries' performance in both dimensions. In the 2018 MDI ranking, top ranks are dominated by European countries, many Sub-Saharan African countries can be found on lower ranks. Over time, the global averages for all three MDI versions are increasing. This positive trend is largely driven by improvements in the achievements dimension. Equity consideration deserve a stronger emphasis in development concepts. However, last years' trend in the equity dimension are optimistic.
Keywords: O15; C43; P48; 330; index; multidimensional; inclusiveness; inclusive development